Democratic deficit critical citizens revisited - Norris, Pippa (Cambridge University Press, 2010)
"This book focuses on 'democratic deficits', reflecting how far the perceived democratic performance of any state diverges from public expectations. Norris examines the reasons behind the democratic deficit and analyzes the consequences for active citizenship, for governance, and ultimately, for democratization"--